2017
DOI: 10.1002/htj.21276
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different loads on structure deformation of “L”‐type large‐diameter buried pipe network based on flow–heat–solid coupling

Abstract: Large‐diameter buried pipelines are widely used because of their energy‐saving advantages and high efficiency. In this paper, an “L”‐type heat pipe network was taken as the research object and was studied using the flow–heat–solid coupling method. The ANSYS Workbench platform was used to simulate heat transfer and the flow of the medium in the pipe network. The pressure and temperature of the flow field and the temperature and deformation of the solid structure under different conditions were calculated. Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…In heat transportation, storage, and conversion, the underground pipeline laying technique has gained attention recently because of suitability, quick construction, and low building cost. A study showed heat transfer analysis of large diameter L-type heat pipe network using the flow heat solid coupling method in the ANSYS workbench platform [48].…”
Section: Background Literaturementioning
confidence: 99%
“…In heat transportation, storage, and conversion, the underground pipeline laying technique has gained attention recently because of suitability, quick construction, and low building cost. A study showed heat transfer analysis of large diameter L-type heat pipe network using the flow heat solid coupling method in the ANSYS workbench platform [48].…”
Section: Background Literaturementioning
confidence: 99%
“…In order to verify the reliability of the proposed method, the pipeline used in literature study [25][26][27] was selected as the research object. According to the geometric model data provided in the literature, as shown in Fig.…”
Section: Verification Of the Thermal-fluid-structure Coupling Calculationmentioning
confidence: 99%